Acute kidney injury in a Malaysian Intensive Care Unit: incidence, risk factors and outcome - Md Ralib, Azrina; Mat Nor, Mohd Basri (Singapore-ANZIC, 2015)
Objectives: Acute Kidney Injury (AKI) is common and carries a high mortality rate. Most epidemiological studies were retrospective and were done in Western populations. To the best of our knowledge, there is no data on the AKI epidemiology based on consensus guideline in our local ICU setting. A prospective study in our population utilising the recent AKI consensus guideline is warranted. This will also allow us to investigate the associated risk factors and outcome.